2021
DOI: 10.3389/fonc.2021.740320
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 in Patients With Hematologic Malignancies: A Single Center Retrospective Study

Abstract: Initial studies that described the novel coronavirus (COVID-19) reported increased morbidity and mortality in patients with cancer. Of this group, patients with hematologic malignancies (HM) had the highest disease severity and death rates. Subsequent studies have attempted to better describe how COVID-19 affects patients with HM. However, these studies have yielded variable and often contradictory results. We present our single-institution experience with patients with HM who were diagnosed with COVID-19 from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 15 publications
0
2
1
Order By: Relevance
“…Our data confirm that a more significant number of COVID-19 cases were diagnosed with leukemia 63.3%; most of the patients recorded 33 (71.74%) in a survived group with leukemia, however; 13 (28.26%) of the survived patients presented with lymphoma comparatives for 9 (64.29%) in the dead group. This result contradicts the finding of Xuejun et al, Who found that most patients with COVID-19 had lymphoid malignancies 28 . This discrepancy may be due to our regional patient population distribution, which has higher rates of leukemia malignancies.…”
Section: Discussioncontrasting
confidence: 78%
“…Our data confirm that a more significant number of COVID-19 cases were diagnosed with leukemia 63.3%; most of the patients recorded 33 (71.74%) in a survived group with leukemia, however; 13 (28.26%) of the survived patients presented with lymphoma comparatives for 9 (64.29%) in the dead group. This result contradicts the finding of Xuejun et al, Who found that most patients with COVID-19 had lymphoid malignancies 28 . This discrepancy may be due to our regional patient population distribution, which has higher rates of leukemia malignancies.…”
Section: Discussioncontrasting
confidence: 78%
“…Autologous hematopoietic stem cell transplantation (HSCT) for relapsed Hodgkin's lymphoma increases the risk of infection by using intensive chemotherapy [ 3 ]. This risk is ongoing given the increased virulence of severe SARS-CoV-2 [ 4 ]. The Center for International Blood and Marrow Transplant Research (CIBMTR) has concluded that coronavirus infection in patients receiving autologous hematopoietic stem cell transplantation has a poor prognosis [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The outbreak of the Coronavirus Disease 19 (COVID-19) began an era of great challenges in the clinical management of patients with hematological malignancies [ 1 ]. In such cases, the immune response to Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) is compromised, thus leading to considerably high morbidity and mortality rates of hematologic patients hospitalized with SARS-CoV-2 infections [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%